CORRELATION OF MICROMETRIC PARAMETERS WITH QUALITY OF OOCYTES IN NILI-RAVI BUFFALOES - M. Nawaz; M. Saleem; M.U. Iqbal; A. Riaz (Journal of Animal and Plant Sciences, 2020)
Detailed visibility of ooplasm plays a pivotal role in advanced reproductive bio techniques (ICSI, SCNT). To improve visibility, oocytes are usually handled after cumulus denuding. This study was conducted to establish buffalo oocyte quality estimation in denuded form. For this purpose, correlations were recognized among the size of oocyte, ooplasm and zona pellucida (ZP) with oocyte quality in Nili-Ravi buffalo. From slaughter house based ovaries, oocytes (n=150) were collected by aspiration of follicles and categorized into A, B, C, and D grades based on the number of layers of cumulus cell. After denuding with hyaluronidase enzyme, the detailed micrometric study was performed under inverted microscope at 40X by using micro imaging software (cellSens Dimension 1.16). The data were analyzed by correlation test using a statistical analysis system (SAS 9.1). The results demonstrated as the followings, the mean oocytes diameter (149.76±0.99µm), the width of zona pellucida (12.84±0.23µm), ooplasm diameter (117.5±0.70µm), oocyte area (17804±136μm²) and ooplasm area (11308.09±75μm2). There was a strong positive correlation between the ooplasm diameter and oocytes diameter in A and B grade oocytes (r=0.7792) as compared to C and D grade oocytes (r=0.5967). However, there was moderate positive correlation between the width of zona pellucida and oocytes diameter in C and D grade oocytes (r=0.6530) as compared to the A and B grade oocytes (r=0.5287). In conclusion, the greater the ooplasm diameter and lesser the width of zona pellucida give rise to the good quality oocytes. Therefore, it is implied that for better developmental competence, the oocytes with bigger ooplasm and thinner zona pellucida should be processed.
Keywords: Nili-Ravi Buffalo oocyte; micrometry; correlation